Glyoxylate cycle and metabolism of organic acids in the scutellum of barley seeds during germination. (July 2016) - Ma, Zhenguo; Marsolais, Frédéric; Bernards, Mark A.; Sumarah, Mark W.; Bykova, Natalia V.; Igamberdiev, Abir U.
Highlights: Glyoxylate cycle is active in scutellum of germinating barley seeds. Citrate and malate are abundant in scutellum and endosperm while succinate is not accumulated. Organic acids produced via glyoxylate cycle can participate in acidification of endosperm. Glyoxylate cycle can support amino acid synthesis in cereals during germination. Operation of the glyoxylate cycle leads to the increase in ATP/ADP and H2 O2 . Abstract: During the developmental processes from dry seeds to seedling establishment, the glyoxylate cycle becomes active in the mobilization of stored oils in the scutellum of barley ( Hordeum vulgare L.) seeds, as indicated by the activities of isocitrate lyase and malate synthase. The succinate produced is converted to carbohydrates via phosphoenolpyruvate carboxykinase and to amino acids via aminotransferases, while free organic acids may participate in acidifying the endosperm tissue, releasing stored starch into metabolism. The abundant organic acid in the scutellum was citrate, while malate concentration declined during the first three days of germination, and succinate concentration was low both in scutellum and endosperm. Malate was more abundant in endosperm tissue during the first three days of germination; before citrate became predominant, indicating that malate may be the main acid acidifying the endosperm. The operation of the glyoxylate cycle coincided with an increase in the ATP/ADP ratio, a buildup of H2 O2 and changes in the redox state of ascorbate and glutathione. It is concluded that operation of the glyoxylate cycle in the scutellum of cereals may be important not only for conversion of fatty acids to carbohydrates, but also for the acidification of endosperm and amino acid synthesis.